Reef-forming polychaetes outcompetes ecosystem engineering mussels - Jaubet, Maria Lourdes (2013)
In order to understand changes in the functioning and the community structure of intertidal ecosystem in sewage-impacted sites, a long-term monitoring coverage study (2004–2011) was carried out on abrasion platforms of the SW Atlantic. The intertidal zone is characterized by the mytilid Brachidontes rodriguezii, an ecosystem engineer. Since the austral spring of 2008, a demographic explosion of an invader polychaetes, Boccardia proboscidea, has produced massive biogenic structures around the sewage discharge outfall. Cover percentage of this polychaete reached almost 100% in sewage-impacted sites but low or no coverage at all in Reference Sites. The density of B. rodriguezii declined due to the biogenic reefs stifles these mytilids. The massive settlement of B. proboscidea among mussels, the rapid growth and the tube construction smothers the mussels in sewage-impacted sites.